Studi Kelayakan Bisnis Telur Asin H-Organik - Opan Arifudin*; Yayan Sofyan; Rahman Tanjung (LPPM Universitas BSI, 2020)
ABSTRACT In order to increase the productivity and effectiveness of the company, it is necessary to hold a business feasibility study that is useful for researching and examining various aspects that support the development of the company. For this reason, this study aims to look at business feasibility studies in the business sector engaged in the production and sale of salted eggs. This research uses descriptive research. This study will examine how the feasibility of H-Organic Salted Eggs, namely research conducted to determine the value of independent variables, either one or more variables without making comparisons or connecting with other variables. The results showed: 1) Viewed from the marketing aspect. the forecast of market demand for insured eggs has been analyzed. it turns out that market demand is very volatile. as well as the market potential which turns out to indicate a demand that has not been fulfilled by the company. Thus the company has the opportunity to be able to increase its production capacity and increase sales distribution stores, 2) Strategic location that allows the company to be able to increase efficiency. through managing raw materials. and managing the availability of labor which is a benefit for the H-Organic Salted Eggs company, 3) With the existence of a new store branch as a form of expansion of the marketing process. as well as influential in increasing the level of sales feasible to be realized, 4) With developments facing the company. then the organizational structure and management system that should be applied must be improved so that it is in accordance with the demands of the company's development, and 5) In conducting the production process. the company does not produce or produce waste that can endanger the surrounding community so that it is safe for the environment. This adds to the positive value and image of the company in the eyes of the community. Keywords: Appropriateness, BusinessABSTRACT In order to increase the productivity and effectiveness of the company, it is necessary to hold a business feasibility study that is useful for researching and examining various aspects that support the development of the company. For this reason, this study aims to look at business feasibility studies in the business sector engaged in the production and sale of salted eggs. This research uses descriptive research. This study will examine how the feasibility of H-Organic Salted Eggs, namely research conducted to determine the value of independent variables, either one or more variables without making comparisons or connecting with other variables. The results showed: 1) Viewed from the marketing aspect. the forecast of market demand for insured eggs has been analyzed. it turns out that market demand is very volatile. as well as the market potential which turns out to indicate a demand that has not been fulfilled by the company. Thus the company has the opportunity to be able to increase its production capacity and increase sales distribution stores, 2) Strategic location that allows the company to be able to increase efficiency. through managing raw materials. and managing the availability of labor which is a benefit for the H-Organic Salted Eggs company, 3) With the existence of a new store branch as a form of expansion of the marketing process. as well as influential in increasing the level of sales feasible to be realized, 4) With developments facing the company. then the organizational structure and management system that should be applied must be improved so that it is in accordance with the demands of the company's development, and 5) In conducting the production process. the company does not produce or produce waste that can endanger the surrounding community so that it is safe for the environment. This adds to the positive value and image of the company in the eyes of the community. Keywords: Appropriateness, Business